1991
DOI: 10.1148/radiology.178.3.1994408
|View full text |Cite
|
Sign up to set email alerts
|

Fungal pulmonary infections after bone marrow transplantation: evaluation with radiography and CT.

Abstract: The authors reviewed 55 pairs of chest radiographs and computed tomographic (CT) studies obtained in 33 febrile bone marrow transplant (BMT) recipients. The images were read separately, without knowledge of the clinical diagnosis. Twenty-one episodes of fungal infection were documented. One chest radiograph showed a pneumonia-like opacity, and 17 showed nodular opacities, five with cavitation. In 20 of 21 episodes, CT showed nodules with cavitation (n = 7), halo (n = 4), hazy margin (n = 5), air bronchogram (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(43 citation statements)
references
References 0 publications
3
37
0
3
Order By: Relevance
“…In this early phase, the histopathological examination demonstrates focus of ischemic lung originating nodules of 1 to 3 cm with central necrosis and hyphae, and surrounding hemorrhage [15,17,19]. This histological finding is demonstrated in the HRCT scan as the halo sign, which was seen in 75% of our cases.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In this early phase, the histopathological examination demonstrates focus of ischemic lung originating nodules of 1 to 3 cm with central necrosis and hyphae, and surrounding hemorrhage [15,17,19]. This histological finding is demonstrated in the HRCT scan as the halo sign, which was seen in 75% of our cases.…”
Section: Discussionsupporting
confidence: 52%
“…The HRCT scan is superior to plain radiographic films in the detection and characterization of pulmonary complications after BMT. This exam is indicated in the presence of clinical manifestations of pulmonary disease with normal or unspecific radiographic findings, and for those patients who do not present clinical improvement despite adequate therapy [9,[14][15][16][17]. Therefore, the HRCT scan allows more effective investigation for patients in the period after BMT, which is of high importance in such patients whose clinical deterioration is fast and lethal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Mori et al (18) and Won et al (19) have found this sign respectively in only 19% and 40% of cases. No cavitation was found in any case, differently from the findings of Kuhlman et al (11) , where cavitation was observed in five of seven cases (71.4%).…”
Section: Discussionmentioning
confidence: 91%
“…There are studies demonstrating that about 50% of neutropenic patients undergoing treatment with chemotherapy, or submitted to bone marrow transplantation, present severe fungal infection at some phase of their evolution (16,18) .…”
Section: Discussionmentioning
confidence: 99%